The invisible art of film music : a comprehensive history - MacDonald, Laurence E. (Scarecrow Press, Inc., 2013)
In this updated and expanded edition of The Invisible Art of Film Music, Laurence MacDonald provides a comprehensive introduction to film music for the general student, the film historian, and the aspiring cinematographer. This volume is a historically structured account of the evolution of music in films and the development of the films themselves. Arranged as a chronological survey from the silent era to the present day, this volume offers readers insight into the vital contribution film scores have made.